The Grammar of Politics: A Brief History of Legislative Language in Britain. Issue 2 (28th February 2017) - Williams, Matthew
Abstract: Legislative language is a crucial, yet somewhat overlooked element of British politics. So how has the language of British legislation changed over the past century? For this study, all 191, 080 pages of legislation enacted between 1900 and 2015 were assessed for changes in the quantity of legislation, and 5, 878 sections of legislation from 1920 to 2015 were analysed for changes to the quality of language. Parts of speech that affect the subject, object and verb of sentences were recorded, giving a novel long‐term study of indeterminacy in legislative language. Findings show that interpreting legislation became increasingly dependent on circumstance and discretion after the war. Change further accelerated after 1975. This reflected a widening gap between public demands placed on government power and the difficulties faced in accommodating these demands.